A composição dos mini-implantes influencia na resistência à fratura na região de buccal shelf? Um estudo com ossos artificiais - CAMPOS , Cássio Bernard Alves (2021)
Introduction: Different means of anchoring have become an essential tool in contemporary orthodontic practice, impacting an expansion of the limits and possibilities of treating cases with different levels of complexity. In this context, extra-alveolar (EA) mini-implants (MI) appeared. Objective: To investigate whether the material composition influences the fracture risk of orthodontic MI used for insertion in the buccal shelf region. Methods: 130 MI were used, divided into 2 groups, being compared for two different metallic alloys (Ti6Al4V and Stainless Steel). Of these, 20 MI of each group were submitted to the fracture test and 15 MI of each group were inserted into artificial bones of 3 mm, 4 mm and 5 mm of cortical thickness at depth of 7 mm to measure insertion torque and removal torque. Nine mini implants from each group were subjected to analysis using a Scanning Electron Microscope (SEM) before and after insertions in artificial bones to assess morphology and possible changes after insertion Results: The steel group had significantly higher insertion torques than the TiA group, regardless of cortical thickness. Torques of 4mm cortical thickness were significantly higher in the steel group. Insertion torques were progressively higher with increasing cortical thickness. Fracture torques were statistically higher in the steel group compared to the TiA group. The regression coefficient demonstrated that both materials were statistically superior to the limit fracture torque value indicated by the manufacturer. SEM analysis did not find changes in the MI surface before and after insertions in artificial bones. Conclusions: Steel proved to be superior to titanium in terms of insertion torque and fracture resistance. Both materials can be used for installation in BS.